SAT0123 The effects of trimethoprim-sulfamethoxazole on disease activity in patients with rheumatoid arthritis. (12th June 2018) - Onishi, A.; Akashi, K.; Hashimoto, M.; Yamamoto, W.; Murata, K.; Katayama, M.; Amuro, H.; Son, Y.; Yoshida, S.; Nagai, K.; Hara, R.; Ebina, K.; et al.
Abstract : Background: Some experimental models suggested bacterial infection, such as periodontal disease and gut microbiota, might be an inciting and aggravating factor in rheumatoid arthritis (RA) 1 . Moreover, medications that have an antibacterial effect such as minocycline and sulfasalazine are used as DMARDs. However, the antibacterial effect itself on disease activity are unknown in patients with RA whereas trimethoprim-sulfamethoxazole (TMP-SMX) is often used for Pneumocystis jirovecii pneumonia (PCP) prophylaxis because PCP is a prevalent and potentially life-threatening opportunistic infection among patients with RA, especially in Japan 2.3 . Objectives: To identify the effect of TMP-SMX on disease activity in patients with RA in a multi-center cohort study (ANSWER cohort study). Methods: RA patients with a sampling interval of less than 1 year and at least two assessment of disease activity were enrolled. Disease activity was assessed using disease activity score 28-CRP (DAS28-CRP). Linear mixed effect models were used to evaluate the trajectories of disease activity in RA patients. Time from baseline, TMP-SMX administration, and their interaction were included as fixed effects while participant identification number and time from baseline were included as random factors. Age, sex, disease duration, RF, ACPA, HAQ, and DMARDs were included as covariates. Results: A total of 49878 samples (mean sampling interval: 49 days) from 3255 patients was included. The median age at baseline was 64.0 years (interquartile range, 53.0 to 71.0 years) with 78.2 % of women (ACPA positivity, 79.2%; RF positivity, 70.8 %). The median DAS28-CRP was 2.83 with 33.8 % of patients taking TMP-SMX at baseline. Patients with taking TMP-SMX had a significantly but minimally better longitudinal trajectory on disease activity than patients without (-0.00012/month, P= 0.009). This result was similar even when patients taking sulfasalazine were excluded from analysis. Conclusions: TMP-SMX has minimal impact on disease activity, and therefore clinical utility of TMP-SMX for controlling disease besides PCP prophylaxis is limited. These results did not support a theoretical effect of bacterial infection on disease activity in RA, although the effect of the other antibiotics on disease activity should be examined. References: [1] Roszyk E, Puszczewicz M. Role of human microbiome and selected bacterial infections in the pathogenesis of rheumatoid arthritis. Reumatologia 2017;55:242-50. [2] Galli M, Antinori S, Atzeni F, et al. Recommendations for the management of pulmonary fungal infections in patients with rheumatoid arthritis. Clin Exp Rheumatol 2017;35:1018-28. [3] Harigai M, Koike R, Miyasaka N, et al. Pneumocystis pneumonia associated with infliximab in Japan. N Engl J Med 2007;357:1874-6. Acknowledgements: None. Disclosure of Interest: None declared